Cyber warfare: a study of Zelenskyy’s social media political performance strategies and effects - Liqiang Wang; Ruonan Wang (Frontiers in Psychology)
During the Russia-Ukraine war, Ukrainian President Volodymyr Zelenskyy has strategically used social media to appeal for international support. This reflects a broader trend of political figures relying on digital platforms to shape public opinion and influence global narratives during crises. This work uses three main analysis methods, content, sentiment and social network analysis. The searched and collected dataset consists 604 valid tweets and 58,100 corresponding comments. The findings show that Zelenskyy employs both textual and visual narratives to construct a war-related agenda, influencing international public discourse. His agenda-setting is most effective in the early stages of the conflict but weakens over time. This study highlights Zelenskyy’s flexibility and adaptability in his media strategy, illustrating the evolving nature of political performance in a globalized media landscape. To maintain effective communication and image-building, leaders must balance audience psychology with the characteristics of digital media.